Very high-power short-duration ablation for pulmonary vein isolation utilizing a very-close protocol—the FAST AND FURIOUS PVI study. Issue 3 (22nd December 2022) - Heeger, Christian-H; Sano, Makoto; Popescu, Sorin Ștefan; Subin, Behnam; Feher, Marcel; Phan, Huong-Lan; Kirstein, Bettina; Vogler, Julia; Eitel, Charlotte; Hatahet, Sascha; Kuck, Karl-Heinz; Tilz, Roland R
Abstract: Aims: The very high-power short-duration (vHP-SD) radiofrequency (RF) ablation concept of atrial fibrillation (AF) treatment by pulmonary vein isolation (PVI) aims for safer, more effective, and faster procedures. Utilizing conventional ablation, the 'close protocol' has been verified. Since lesion formation of vHP-SD ablation creates wider but shallower lesions we adapted the close protocol to an individualized and tighter 'very-close protocol' of 3–4 mm of inter-lesion distance (ILD) at the anterior and 5–6 mm at the posterior aspect of the left atrium using vHP-SD only. Here, we evaluated the safety and efficacy of vHP-SD ablation for PVI utilizing a very-close protocol in comparison with standard ablation. Methods and results: A total of 50 consecutive patients with symptomatic AF were treated with a very-close protocol utilizing vHP-SD (vHP-SD group). The data were compared with 50 consecutive patients treated by the ablation-index-guided strategy (control group). The mean RF time was 352 ± 81 s (vHP-SD) and 1657 ± 570 s (control, P < 0.0001), and the mean procedure duration was 59 ± 13 (vHP-SD) and 101 ± 38 (control, P < 0.0001). The first-pass isolation rate was 74% (vHP-SD) and 76% (control, P = 0.817). Severe adverse events were reported in 1 (2%, vHP-SD) and 3 (6%, control) patients ( P = 0.307). A 12-month recurrence-free survival was 78% (vHP-SD) and 64% (control, P = 0.142). PVI durability assessed during redo-procedures was 75% (vHP-SD) vs. 33% (control, P < 0.001). Conclusions: PVI solely utilizing vHP-SD via a very-close protocol provides safe and effective procedures with a high rate of first-pass isolations. The procedure duration and ablation time were remarkably low. A 12-month follow-up and PVI durability are promising.